De amores e desamores em Valter Hugo Mãe - Rocha, Sidnei Alves da (2022)
The present thesis aims at the comparative study of the representations of love and lack of love (which also involve anger and hate) in the novels o nosso reino, o remorso de baltazar serapião, o apocalipse dos trabalhadores, a máquina de fazer espanhóis, O filho de mil homens, A desumanização e Homens imprudentemente poéticos, by the Portuguese writer Valter Hugo Mãe, released between 2004 and 2016. It seeks to analyze the nuances of these feelings unfolded in their various faces and perspectives, such as those present in the works that make up the research corpus. For this analysis, we resort to theoretical-critical studies that include, among others: reflections on the contemporary novel; an overview of Contemporary Portuguese Literature, and the writer's critical fortune (mainly anchored by Arnaut, Ceia, Perrone-Moisés, Real, Nogueira, Reis). In addition, we dialogue with philosophy through the study of prominent Greek loves covered addressed in this thesis – eros, philia, and agape; the concept of love throughout history and its presence in literature; of the writer's narrative constructions to create the representations of love, disaffection, anger and hate in his characters. In order to do so, we resort to the reflections of scholars such as Comte-Sponville, Bauman, Krznaric, May, Aristotle, Plato, Seneca, who help us to understand this picture of feelings, sensations, and passions according to Aristotle's Rhetoric. Considering that, in the context of contemporary Portuguese literature, Mãe is one of the most relevant writers with an already consolidated work, this thesis seeks to fill a gap in his current critical fortune through a comparative analysis of the set of his novels around an expensive matter to literature – love – one of the most important feelings in all historical contexts and, therefore, a topos in the history of literature itself. In conclusion, even when the characters' plots and actions prove the opposite, love prevails over other passions, in a process that leads us to understand this author's literature as humanized and humanizing, evidencing that passions are also learned.